Learning and innovation in enterprises - (:unkn) unknown (Publications Office of the European Union, 2012)
"What are the links between work organisation, workplace learning, training and innovation? How can our workplaces become good environments for learning and innovation? Are European companies applying any policies or public programmes that combine innovation and skills development? If so, how do these programmes operate? Covering the EU-27 plus Norway, this report looks at innovation and learning in enterprises and examines the role that training and learning-conducive work environments can play in making companies more innovative." (Hrsg. , BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; S 5 Organisationsentwicklung; S 3.2 Unternehmen und Behörden; I 2.2 Europa; Lernende Organisation; Lernkultur; Lernen am Arbeitsplatz; Innovation; Europa